The Debate as a Teaching Aid in the Mirror of the Establishment of the Hydroelectric Power Station of Ikervár (Training and Practice : Journal of Educational Sciences, 2016)
The article presents the debate about the establishment of the hydroelectric power station of Ikervár forming a notion in this way of the social-economic and technological-educational development of Hungary and of the Western-Transdanubian region of the period and of the development of scientific professional training.During the debate they had to decide whether to apply further the source of energy existing at that time (coal-gas) or to yield to use electricity produced by the novelty, the power of water. The topic of the essay and the debate which can be organized about it can be used in education, in its modernization and the preparation of students for the future.The aim of the author is to present the questions concerning the topic not only in a scientific but in an educational way as well and to publish them possibly.